Enhancing SEM signature via bistatic radar configuration of small bisectors - Aldhubaib, Faisal (IET radar, sonar & navigation, 2022)
The paper assesses the feasibility of finding bistatic directions of minimum bisectors subject to resonant frequency and polarisation diversities to improve the robustness of the resonance signature when extracted from the late time radar response. The general approach consists of three assessments, where the first assessment utilises the scattering frequency data (non‐coherent) to determine if there are bistatic directions of small bisectors per reference resonant frequency and polarisation basis. The second assessment evaluated the correlation between the two targets' incident and scattering directions and confirmed that some directions enhanced the discriminative potential. The third assessment utilised the cumulative sum and the extracted resonant distribution from the time data (coherent) of the bistatic directions to determine the degree of signature enhancement by using a minimum error criterion between the reference and extractable mode frequencies with onset shift. The assessments were qualitative and concluded that the third resonance with a left circular basis could outperform other resonants in discriminative potential. Henceforth, the bistatic configuration improves the strength of this most discriminative resonant mode to allow the maximum utilisation of the SEM signature in the identification operation of aircraft targets.